Pengaruh Rangkap Jabatan Direksi, Hubungan Politik, Pergantian Auditor dan Tekanan Eksternal terhadap Potensi Kecurangan Laporan Keuangan - Fabian, Reynara Rizky; Challen, Auliffi Ermian (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study was conducted to determine the impact of dual positions of the board of directors, political connections, and external pressures on the potential for financial statement fraud in non-financial state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. The research method used is quantitative, specifically associative causal relationships, utilizing secondary data from non-financial SOEs listed on the IDX during the 2018-2023 period. The sampling technique employed is purposive sampling with specific criteria. The data analysis method used is multiple linear regression with SPSS version 26. The results of the study indicate that the dual roles of the board of directors and auditor changes have a positive impact on the potential for financial statement fraud. Meanwhile, political connections and external pressures do not significantly affect the potential for financial statement fraud. Overall, from an Islamic perspective, financial statement fraud is seen as having a negative relationship with Islamic norms, making it inconsistent with Islamic teachings.